PENGARUH DISIPLIN KERJA, MOTIVASI, KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN STUDI PADA PT. BUMI BARITO UTAMA CABANG BANJARMASIN - Alamsyah Yunus; Ahmad Alim Bachri (Universitas Lambung Mangkurat, 2013)
This study aims to determine the influence of labor discipline, motivation and leadership as an independent variable either partially or simultaneously on employee job satisfaction as the dependent variable on the company PT. Bumi Barito Main branch of Banjarmasin. The research uses a quantitative approach with a sample of 39 employees of PT. Bumi Barito Main branch of Banjarmasin. Measurement variables by using a Likert scale with a score of 1 to 5 scale. Data were analyzed using multiple linear regression statistical techniques and to test the significant level using the F test and t-test with SPSS all assistance. Partial results of the study showed that labor discipline and a significant positive effect on job satisfaction, motivation variable positive and significant effect on job satisfaction and leadership variable positive and significant effect on job satisfaction. The results showed that the variables simultaneously work discipline, motivation and leadership, and a significant positive effect on job satisfaction. Of the three independent variables studied variables that have the greatest influence / motivation is the dominant variable in the regression coefficient of 0.464 or 46.4% on job satisfaction compared with the other two independent variables.